Empleo de una ß-galactosidasa comercial de Kluyveromyces lactis en la hidrólisis de lactosuero (2012)
ABSTRACT: The whey is the largest waste subproduct of the dairy industry. Due to its high values of BOD is considered a source of water and soil contamination when discarded without any treatment. An alternative for the disposal of this agroindustrial waste is its application as a culture medium for various fermentation processes after an enzymatic hydrolysis thus ensuring a greater availability of fermentable sugars for subsequent application in biotechnology, environment and / or food. Objective To evaluate the effects of pH, temperature and enzyme concentration on whey using a commercial β-galactosidase from Kluyveromyces lactis, and determine the kinetic parameters of the enzyme. Materials and methods The hydrolysis of lactose was performed in buffered solutions of lactose and in whey as well, 5 levels were evaluated for pH (4.5-8.5), temperature (25°C-65°C) and enzyme concentration (0.025 g/L to 0.5 g/L), all the experiments were performed in triplicate in Erlenmeyer flask (100 mL) and analyzed using the GraphPad Prism software. Results We found that the best conditions of pH and temperature for the whey hydrolysis were at 6,5°C and 45°C respectively. According to the kinetic results, the enzyme presented competitive inhibition for galactose with a Km equal to 8.01x10-2 M, Ki of 6.85x10-2 M and Vmax of 1.86x10-2 molmg-1min-1. Conclusions The best conditions of pH and temperature were 6.5°C and 45°C respectively, a 100% of hydrolysis was achieved in one hour with 0.1 g/L of enzyme. Furthermore, it was shown that the reaction rate of the enzyme is inhibited by galactose.